Circle Passes through the Origin and Centre Lies on x-axis

We will learn how to find the equation of a circle passes through the origin and centre lies on x-axis.

The equation of a circle with centre at (h, k) and radius equal to a, is (x - h)\(^{2}\) + (y - k)\(^{2}\) = a\(^{2}\).

When the circle passes through the origin and centre lies on x-axis i.e., h = a and k = 0.

Then the equation (x - h)\(^{2}\) + (y - k)\(^{2}\) = a\(^{2}\) becomes (x - a)\(^{2}\) + y\(^{2}\) = a\(^{2}\)

Circle Passes through the Origin and Centre Lies on x-axisCircle Passes through the Origin and Centre Lies on x-axis

If a circle passes through the origin and centre lies on x-axis then the abscissa will be equal to the radius of the circle and the y co-ordinate of the centre will be zero. Hence, the equation of the circle will be of the form:

(x - a)\(^{2}\) + y\(^{2}\) = a\(^{2}\)

⇒ x\(^{2}\) + y\(^{2}\) - 2ax = 0

 

Solved example on the central form of the equation of a circle passes through the origin and centre lies on x-axis:

1. Find the equation of a circle passes through the origin and centre lies on y-axis at (0, -2).

Solution:

Centre of the lies on y-axis at (0, -2)

Since, circle passes through the origin and centre lies on x-axis then the abscissa will be equal to the radius of the circle and the y co-ordinate of the centre will be zero.

The required equation of the circle passes through the origin and centre lies on y-axis at (0, 2) is

(x + 7)\(^{2}\) + y\(^{2}\) = (-7)\(^{2}\)

⇒ x\(^{2}\) + 14x + 49 + y\(^{2}\) = 49

⇒ x\(^{2}\) + y\(^{2}\) + 14x = 0

 

2. Find the equation of a circle passes through the origin and centre lies on x-axis at (12, 0).

Solution:

Centre of the lies on x-axis at (12, 0)

Since, circle passes through the origin and centre lies on x-axis then the abscissa will be equal to the radius of the circle and the y co-ordinate of the centre will be zero.

The required equation of the circle passes through the origin and centre lies on x-axis at (12, 0) is

(x - 12)\(^{2}\) + y\(^{2}\) = 12\(^{2}\)

⇒ x\(^{2}\) - 24x + 144 + y\(^{2}\) = 144

⇒ x\(^{2}\) + y\(^{2}\) - 24x = 0





11 and 12 Grade Math 

From Circle Passes through the Origin and Centre Lies on x-axis to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.